Legal Aid for the Poor in the Perspective of Fiqh Tanfiziyyah - Agung Pratama, M. Rafirsa; Akbar Maliki, Ibnu; Anes Junilia, Devi (State of Islamic Institute Langsa, 2023)
This research aims to describe the legal aid for the poor from the perspective of fiqh tanfiziyyah at the Menang Jagad Legal Aid Institute, North Lampung Regency. This research is a qualitative, in which data collection is done by observation and in-depth interviews. The data was analysed by using inductive method to get conclusion. This research found that first, the implementation of Regional Regulation Number 4 of 2013 concerning the provision of legal aid in North Lampung Regency is an effort to provide legal aid to the poor in accordance with the laws and regulations contained in Law Number 16 of 2011 concerning legal aid, and Regional Regulation Number 04 of 2013, as well as a derivative of Regent Regulation Number 18 of 2014. Second, the implementation of the provision of legal aid in North Lampung Regency through the legitimacy of Regional Regulation Number 4 of 2013 in the perspective of fiqh siyasah tanfiziyyah is in accordance with the norms of Islamic law and is obliged to provide services. Because in Islam itself it has been confirmed that every Indonesian citizen in his position before the law is the same. Namely, as an obligation of law enforcement and justice for all individuals.